2021
DOI: 10.3390/jcm10050936
|View full text |Cite
|
Sign up to set email alerts
|

CPAP Therapy Termination Rates by OSA Phenotype: A French Nationwide Database Analysis

Abstract: The nationwide claims data lake for sleep apnoea (ALASKA)—real-life data for understanding and increasing obstructive sleep apnea (OSA) quality of care study—investigated long-term continuous positive airway pressure (CPAP) termination rates, focusing on the contribution of comorbidities. The French national health insurance reimbursement system data for new CPAP users aged ≥18 years were analyzed. Innovative algorithms were used to determine the presence of specific comorbidities (hypertension, diabetes and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
54
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(60 citation statements)
references
References 34 publications
4
54
2
Order By: Relevance
“…Moreover, only patients with at least one follow-up visit were included in our study, thus potentially corresponding to a selection of a more responsive population of OVS with favorable outcomes. Indeed, recent data suggest that the CPAP termination rate is higher in the association of COPD and OSAS but at one year this difference do not exceed 5% [ 32 ]. Therefore, the impact on our results is expected to be limited.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, only patients with at least one follow-up visit were included in our study, thus potentially corresponding to a selection of a more responsive population of OVS with favorable outcomes. Indeed, recent data suggest that the CPAP termination rate is higher in the association of COPD and OSAS but at one year this difference do not exceed 5% [ 32 ]. Therefore, the impact on our results is expected to be limited.…”
Section: Discussionmentioning
confidence: 99%
“…Several previous publications have raised the clinical problem of poor adherence of CPAP in OSA. Pepin et al [ 22 ] analyzed the CPAP therapy of OSA patients from a French nationwide database analysis (n: 480,000 subjects) and found that overall CPAP termination rates after 1, 2 and 3 years were 23.1, 37.1 and 47.7% respectively and raised the importance of phenotyping and personalized care approaches that determine the most appropriate. In the SAVE study, McEvoy et al [ 6 ] found that CPAP adherence at the beginning of the study was 5.3 h/night, and after 24 months of follow-up, it was reduced to 3.4 h/night (n:1121, 5 different countries).…”
Section: Discussionmentioning
confidence: 99%
“…Recently described telemedicine interventions focused on improving CPAP adherence are applied during the first weeks/months after CPAP is prescribed, when adherence is relatively acceptable [15,16]. However, it is well known that the patient's adherence with this treatment decreases [16][17][18][19][20][21][22] over time. Therefore, novel interventions addressed to improve CPAP adherence in patients already in long-term treatment are required.…”
Section: Introductionmentioning
confidence: 99%
“…In one early study, compliance after 5 years was only 68% [ 2 ]. Pepin et al, have recently published results of a nationwide study on CPAP adherence and found that termination rate after 3 years of treatment was almost 50% [ 3 ]. Other studies based on data from a large cloud database reported 90 days adherence at the level of only 75% [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…There are numerous factors that may affect adherence to CPAP treatment. For instance, several demographic and clinical variables, e.g., age, sex, BMI (body mass index), race, apnoea-hypopnoea index (AHI), Epworth Sleepiness Scale (ESS) score and the presence of comorbidities were shown to have an effect on compliance [ 2 , 3 , 6 , 7 ]. Conversely, in the SAVE (The sleep apnea cardiovascular endpoints) study only compliance at 1 month and the presence of side effects of CPAP therapy were predictors of its use at 12 months [ 8 ].…”
Section: Introductionmentioning
confidence: 99%